2015
DOI: 10.1155/2015/534176
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Extraocular Sebaceous Carcinoma Recurring after Mohs Micrographic Surgery

Abstract: Sebaceous carcinomas (SC) are rare adnexal tumors with possible aggressive behavior usually arising in the head and neck region of adults in the seventh decade of life. Treatment has traditionally been with surgical excision with 5-6 mm wide margins but Mohs micrographic surgery (MMS) has also been reported as an effective treatment modality. We present a case of a Caucasian female renal transplant patient with a rapidly enlarging nodule on the left preauricular cheek that was excised with MMS with negative ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Including this case, there are 4 individual case reports of extraocular SC treated by MMS. 24,36,45 Radiation Therapy…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Including this case, there are 4 individual case reports of extraocular SC treated by MMS. 24,36,45 Radiation Therapy…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Although in this series, extraocular SC have a different clinical outcome from ocular SC, there have been rare cases of extraocular SC reported in the literature that have shown a more aggressive behavior. 11,28,31,43,44 Only 2/62 cases of extraocular SC had multiple recurrences and none of them metastasized as opposed to our cases of ocular SC, wherein 54% of cases were locally aggressive with multiple recurrences and 5 cases metastasized. Several factors may account for some of the difference in behavior between ocular and extraocular SC.…”
Section: Sebaceousmentioning
confidence: 60%
“…Many studies have reported that a subset of these tumors can have a high risk of local recurrence with some cases being capable of developing metastases. 1,5,[28][29][30][31] Most studies reported in the literature have described ocular SC in detail, but have failed to compare them with extraocular SC.…”
Section: Discussionmentioning
confidence: 99%
“…Mohs micrographic surgery has also been used as an alternative, with local recurrence rates of 11-12% for ocular lesions [18,19]. Extending this technique to extraocular cases, Mohs surgery has also been used in a few cases of sebaceous carcinoma in cosmetically-sensitive areas such as the cheek [7,20]. Despite these favorable studies, both Mohs techniques and wide excision may be problematic in multifocal cases with "skip areas" [19].…”
Section: Case Discussionmentioning
confidence: 99%